2014
DOI: 10.1088/0953-8984/26/15/155802
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of band alignments in the p-type hosts BaM2X2(M= Cu, Ag;X= S, Se)

Abstract: Abstract. The electronic structures of four semiconductor compounds BaCu 2 S 2 , BaCu 2 Se 2 , BaAg 2 S 2 , and BaAg 2 Se 2 are studied by density functional theory using both semi-local and hybrid functionals. The ionization energies and electron affinities were determined by aligning the electronic states with the vacuum level by calculating the electrostatic profile within a supercell slab model. The ionization energy and electron affinity of the compounds were calculated using the Heyd-Scuseria-Ernzerhof (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Thus, Ag 2 BaS 2 is a direct band gap semiconductor with a band gap of 1.95 eV. Note that our direct band gap value of 1.95 eV calculated with HSE06 closely matches the previous HSE06 band gap value of 2.01 eV [ 34 ] calculated by Aditi Krishnapriyan et al To the best of our knowledge, no experimental study has been previously reported on Ag 2 BaS 2 . From Figure 2 b and the Figure S4 of Supplementary Materials , the valence band maximum is derived from S-p states and conduction band derived from Ag-s states.…”
Section: Resultssupporting
confidence: 89%
“…Thus, Ag 2 BaS 2 is a direct band gap semiconductor with a band gap of 1.95 eV. Note that our direct band gap value of 1.95 eV calculated with HSE06 closely matches the previous HSE06 band gap value of 2.01 eV [ 34 ] calculated by Aditi Krishnapriyan et al To the best of our knowledge, no experimental study has been previously reported on Ag 2 BaS 2 . From Figure 2 b and the Figure S4 of Supplementary Materials , the valence band maximum is derived from S-p states and conduction band derived from Ag-s states.…”
Section: Resultssupporting
confidence: 89%
“…However, this strategy looks appealing as the p states of the chalcogen atoms are usually higher and therefore make the compound more prone to be p -doped. Recent calculations suggest that this is the case for Ba(Cu, Ag) 2 (S, Se) 2 compounds36.…”
mentioning
confidence: 94%
“…The crystal structure and transport properties of BaCu 2 Ch 2 (Ch = S, Se and Te) have been studied by few groups to date. [19][20][21][22][23][24][25][26] For Ch = S and Se, two structuretypes can be stabilized: the orthorhombic BaCu 2 S 2 -type and the tetragonal ThCr 2 Si 2 -type. [20][21][22][23] Only the BaCu 2 S 2 structure has been reported for BaCu 2 Te 2 .…”
Section: Introductionmentioning
confidence: 99%